1992
DOI: 10.1007/bf00338048
|View full text |Cite
|
Sign up to set email alerts
|

Migration of cranial neural crest cells to the pharyngeal arches and heart in rat embryos

Abstract: The existence of a neural crest cell migration pathway from occipital levels of the hindbrain into the heart was suspected in mammalian embryos because it had previously been identified in avian embryos and because the Di George anomaly, an association between craniofacial and cardiac malformations, is most easily explained on the basis of abnormal neural crest cell migration to all of the affected structures. In order to demonstrate the existence of this pathway, neural crest cells were labelled in situ in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 29 publications
1
61
0
Order By: Relevance
“…Recent studies have shown, however, that some precursors of the OFT endocardium and mesenchyme (but not those of the AV endocardium) migrate to the heart via the cephalic paraxial and lateral mesoderm (Noden, 1991). Furthermore, experiments conducted with chick-quail chimeras (Phillips et al, 1987) and in rat embryos (Fukiishi and Morriss-Kay, 1992) have demonstrated that cells from the neural crest at the level of the first three to four occipital somites also enter the cushion tissue of the OFT. No neural crest contribution has been identified in the AV region.…”
Section: Msx-i Expression In Cushion Tissue Of the Oftmentioning
confidence: 99%
“…Recent studies have shown, however, that some precursors of the OFT endocardium and mesenchyme (but not those of the AV endocardium) migrate to the heart via the cephalic paraxial and lateral mesoderm (Noden, 1991). Furthermore, experiments conducted with chick-quail chimeras (Phillips et al, 1987) and in rat embryos (Fukiishi and Morriss-Kay, 1992) have demonstrated that cells from the neural crest at the level of the first three to four occipital somites also enter the cushion tissue of the OFT. No neural crest contribution has been identified in the AV region.…”
Section: Msx-i Expression In Cushion Tissue Of the Oftmentioning
confidence: 99%
“…Most of the bone and cartilage in the craniofacial region arises from transient structures called pharyngeal arches (Fukiishi andMorriss-Kay, 1992, Bronner-Fraser, 1995), which are populated by cranial neural crest cells (NCCs). These NCCs migrate from the neuroectoderm of the posterior midbrain and hindbrain to the arches while undergoing an epithelial to mesenchymal transition (Le Douarin, 1982, Tosney, 1982.…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, chickens have a right-sided aortic arch, bilateral ducti arteriosi, and bilateral brachiocephalic arteries (Brown and Baldwin, 2006). Cell labeling and fate mapping experiments in mice (Waldo et al, 1999;Yamauchi et al, 1999;Jiang et al, 2000;Li et al, 2000;Pietri et al, 2003) and rat (Fukiishi and Morriss-Kay, 1992) suggest a conservation of function of the neural crest in mammalian cardiovascular development. There are also multiple genetic and teratogenic alterations in mouse and human that result in a similar phenotype to that of chick neural crest ablation (NCA).…”
Section: Introductionmentioning
confidence: 99%